Gastrointestinal parasite control during prepuberty improves mammary parenchyma development in holstein heifers - Perri, Adrián Francisco (2013)
Parasitism during development impairs normal growth and delays the onset of puberty through altered hormone profiles, including insulin-like growth factor one (IGF-1).Asmammary gland development during prepuberty is strongly dependent on IGF-1, we determined if antiparasitic treatment during this stage of growth improved mammary gland development. One group of Holstein heifers was treated monthly, rotationally with antiparasitic drugs from birth to 70 weeks of age, a second group was untreated. Treated heifer calves had between 56% and 65% less EPG counts than untreated ones. Presence of Ostertagia, Cooperia, Haemonchus and Trichostrongylus was demonstrated. Treatment effectively advanced the onset of puberty and increased IGF-1 levels. At 20, 30, 40 and 70 weeks of age biopsies from the mammary gland were taken and histological sections were prepared and stained with hematoxylin–eosin. Pictures were analyzed to compare parenchyma area in relation to total mammary tissue between groups. Mammary samples from treated heifers had higher ratios of parenchyma/total area than untreated ones. As mammary development during prepuberty is crucial for mammary performance during lactation, these results add new evidence to the importance of gastrointestinal parasite control in heifers